Making Global Trade Work for People : Making the Trading System Work for Everyone. - Malhotra, Kamal (Earthscan, 2003)
The world's trade regime is promoted by international agencies and most governments as the best way to lift the poor out of poverty and achieve sustainable development. But does it contribute to human development or not? This reassessment looks in detail at the way it has worked under the GATT and under the World Trade Organization and analyses how it is working and how it can be improved. The book aims to make major contribution to the debates surrounding globalization and the impact of trade on the poor on social stability and on the environment. It is intended to provide a benchmark for fut.